Gastropods Community Structure in the Mangrove Ecosystem in the Teluk Buo, Bungus Sub-district,Teluk Kabung District, Padang, Sumatera Barat Province - Efi Nuryanti; Adriman '; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Teluk Buo mangrove forest is one of tourist destination in the Sumatera Barat Province. The input of pollutant originated from anthropogenic activities, however, reducing the water quality and as a consequence negatively affects the mangrove ecosystem as well as the associated organisms, including gastropods. To understand the community structure of gastropods in the mangrove ecosystem, a research was conducted on February 2017. There were 3 line transects and in each line, 9 plots (1mx1m) were placed. The gastropods present in the plots were collected manually everyday for 2 weeks period. Result shown that there were 7 gastropods species present, they were Nerita lineata, Nerita undata, Terebralia sulcata,Telescopium telescopium, Cerithidea quadrata, Littoraria melanostoma and Littoraria scabra. The gastropods abundance was ranged from 1.741 to 5.963 organisms/ha. The value of diversity index was (H’) 0.821-2.385, the dominance index (C) was 0.219-0.704, and the uniformity index (E) was 0.118-0.584. The water quality parameters are as follows: temperature was 29-310C; pH was 7.3-7.5 and salinity was 25-34 0/00. Gastropods Community Structure in the Mangrove Ecosystem in the Teluk Buo has been disturbed and the dominant species (T. sulcata).Keywords:Gastropods, Mangrove Ecosystem, Teluk Buo, Water quality